2022
DOI: 10.1038/s41598-022-12681-9
|View full text |Cite
|
Sign up to set email alerts
|

IFN-τ mediated miR-26a targeting PTEN to activate PI3K/AKT signalling to alleviate the inflammatory damage of bEECs

Abstract: Endometritis is the failure of embryo implantation and an important cause of infertility in dairy cows. IFN-τ is a type I interferon unique to ruminants. In regulating the process of inflammatory response, IFN-τ can be expressed through MicroRNAs (miRNAs) to regulate the process of inflammation. However, IFN-τ regulates lipopolysaccharide (LPS)-induced inflammatory injury of bEECs through the highly conserved miR-26a in mammals, and the mechanism remains unclear. Bovine endometrial epithelial cells (bEECs)were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, in the current study, 9 of the 20 genes found flanking the top significant SNPs were discovered to be linked to the phosphatidylinositol-3-kinase/protein kinase B (PI 3 K/Akt) pathway. The PI 3 K/Akt pathway has been recently discussed in terms of its essential role in signal transduction, cell proliferation, apoptosis, and autophagy and its correspondence to pathogenesis within bovine endometrial epithelial cells [64]. The activated pathway phosphorylates Akt downstream, and active Akt has been found to deter the fusion of the autophagosome to the lysosome, allowing for the survival of pathogenic materials and promoting infection [65,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the current study, 9 of the 20 genes found flanking the top significant SNPs were discovered to be linked to the phosphatidylinositol-3-kinase/protein kinase B (PI 3 K/Akt) pathway. The PI 3 K/Akt pathway has been recently discussed in terms of its essential role in signal transduction, cell proliferation, apoptosis, and autophagy and its correspondence to pathogenesis within bovine endometrial epithelial cells [64]. The activated pathway phosphorylates Akt downstream, and active Akt has been found to deter the fusion of the autophagosome to the lysosome, allowing for the survival of pathogenic materials and promoting infection [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…These secondary pathways work to inhibit, activate, and compete with the activity of PI 3 K/Akt and, consequently, regulate autophagosome elongation, maturation, and termination and the autophagy process [70][71][72]. The PI 3 K/Akt pathway was considerably discussed for its role in bovine physiology including oocyte competence, immune responsiveness, milk fat synthesis, bacterial resistance, vascular homeostasis, and angiogenesis [64,[73][74][75][76]. Our study reports the link between the development of uterine infections in dairy cattle and the PI 3 K/Akt pathway, considering its major role in pathogenesis and the immune response.…”
Section: Discussionmentioning
confidence: 99%